TECHNOLOGY 4.0 ERA INVESTMENT DECISIONS FOR MILENIALS AND GENERATION Z - Thezar Fiqih Hidayat Hasibuan; Vanisa Meifari; Iskandar Muda; Sambas Ade Kesuma (RADJA PUBLIKA, 2023)
Almost nearly 60% of all investors in Indonesia's capital market are members of Generation Z, or millennials, who are under 30 years old. The development of Era 4.0 technology has made it easier to obtain information and current trends. As a consequence, the aim of this study is to examine in detail how to make investment decisions in the technology era of 4.0. According to the study, the research method used is qualitative research with the Grounded Theory Approach, which utilizes a number of methodical phases to develop theory, including Approach Stages, Theoretical Sampling, Constant Comparative Data Analysis Approach, A Core Category, Theory Generation, and Memo. According to the findings of a review of 21 literatures, there are three key steps that should be taken to increase financial behavior: (1) increasing financial literacy, which involves learning financial terms and ideally integrating them into institutions or promoting them through training; (2) understanding and knowing the company's portfolio; and (3) increasing financial behavior, which involves increasing experience in investing so that it is more instinctive.